CRITICAL EXPONENTS OF REGGEON FIELD-THEORY - Cardy, J (1977)
By using the method of Lipatov to determine the behavior of perturbation theory at large order, we derive a convergent numerical procedure for the calculation of the critical exponents of Reggeon field theory, based on the loop expansion and the ε{lunate} expansion. We find the results γ = -0.26 ± 0.02, z = 1.13 ± 0.01 and λ = 0.49 ±0.01. © 1977.